Cheders and Melameds in the Memories of Young Jews from the Inter-War Period - Cukras-Stelągowska, Joanna (Paedagogia Christiana, 2018)
The article attempts to create a collective portrait of cheders and teachers working in them (melameds) during the inter-war period. Education in cheders was an extremely important stage of development for Jewish boys. It determined their further educational and professional careers and prepared them for full participation in Jewish communities. These issues are analysed based on the works of historians and diaries using the method of exemplification. The analysis includes autobiographies of young Polish Jews from the inter-war period from the collections of the YIVO Institute for Jewish Research in New York. The article also tries to show the process of changes within religious education, the main reasons for attacks at traditional schools and attempts to reform them. The image of cheders conveyed in diaries is part of this critical trend, but it is not homogeneous. Definitely more positive accounts can be found in the diaries of young Jews who attended reformed cheders.